Antifungal activity of Bacillus sp. against Fusarium sp. on intensive farmed striped catfish in Vinh Long Province, Vietnam - QUACH VAN CAO THI; THANH TRAN; TRUONG QUOC TAT; TAN PHAT CHAU (Society for Indonesian Biodiversity, 2024)
Abstract. Thi QVC, Tran T, Tat TQ, Chau TP. 2024. Antifungal activity of Bacillus sp. against Fusarium sp. on intensive farmed striped catfish in Vinh Long Province, Vietnam. Biodiversitas 25: 2602-2611. Fungal diseases often appear and cause significant losses in aquaculture in Vietnam and many other countries around the world. Therefore, the study's objective was to identify and assess Bacillus's inhibitory action against Fusarium sp., which causes swollen swim bladder disease in striped catfish, in order to minimize the usage of antibiotics, which may be harmful to both human health and the environment. As a result, 34 strains of Bacillus were obtained from samples of sludge, pond water, and the intestines of intensively farmed Pangasius in Vinh Long Province of the Mekong Delta. Inhibitory activity of the fungal spores of isolated Bacillus isolates was performed using the diffusion well method. The findings revealed that twenty out of thirty-four bacterial strains exhibited spore inhibitory activity after 3 days of incubation at 30°C. Among them, six out of twenty bacterial strains had the strongest spore inhibitory activity, with inhibition diameters ranging from 15-23 mm. Additionally, six bacterial strains with strong spore inhibitory activity also secreted extracellular enzymes such as amylase, chitinase, cellulase, and protease. Sequencing results showed that strain BC11 had a 99.37% similarity to the reference Bacillus on GenBank. The findings of the study serve as the foundation for additional research into the production of probiotics to manage pathogenic fungus in striped catfish, which could provide a different approach to lowering the need for antibiotics in the future.